Molecular phylogeny of the insect order Hymenoptera: apocritan relationships. - Dowton, M (1994)
Phylogenetic relationships among the major groups of hymenopteran insects were investigated by using comparative sequence information from the mitochondrial 16S rRNA gene. The placement of the ectoparasitic Stephanidae as the sister group to the remaining Apocrita confirmed ectoparasitism as the ground plan biology for the Apocrita. Endoparasitism evolved at least eight times within the Apocrita, and the consequent association with polydnaviruses and virus-like particles evolved at least three times. The Evaniomorpha were consistently placed as basal to the remaining Apocrita but were not resolved as monophyletic. The Gasteruptiidae were resolved as the sister group to the Evaniidae, but the relationship between the Trigonalyoidea and the Evanioidea was unclear. The Proctotrupomorpha (sensu Rasnitsyn) was resolved by topology-dependent permutation tail probability (T-PTP) testing as monophyletic, with strong evidence for a sister group relationship between the Platygastroidea and the Chalcidoidea. Strong evidence was found for the monophyly of the Ichneumonomorpha (Ichneumonidae + Braconidae) and the sister-group relationship between the Aculeata (Vespomorpha) and the Ichneumonomorpha.